Ethephon-induced shoot production in two cultivars of gentian cultured in vitro : anatomical, morphological and physiological aspects associated with endogenous balance of auxin and cytokinin : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science at Massey University, Palmerston North, New Zealand - Keshavarzi, Marzieh (Massey University, 2017)
For gentian as an export-orientated ornamental crop in NZ, the research within this thesis was motivated by the industry goal of producing highly branched propagules, in order to make high quality pot plants. As part of the in vitro propagation system, application of ethephon as a plant growth regulator (PGR), increased the formation of shoots from nodal explants of the cultivar ‘Little Pinkie’ but not in ‘Showtime Diva’. While only two shoots were expected to arise from a metamer of gentian, a maximum of 20 shoots developed from explants of ‘Little Pinkie’, at 40 mg.L-1 ethephon. Therefore, the research undertaken within this thesis focussed on investigating the mechanism by which shoot formation in explants of gentian was influenced. Main objectives were to investigate the origin of high shoot numbers, the effect of ethephon on shoot number and the underlying mechanisms behind the ethephon’s effect. As a results of these studies it was proposed that a possible underlying mechanism was the effect of ethephon on auxin/cytokinin balance. Both light and scanning electron microscopy were utilised to identify the type of buds that shoots originated from in both cultivars of gentian. Shoots arising at the node of ‘Little Pinkie’ typically had a combination of axillary, co-lateral and adventitious origins. Number of adventitious shoots increased in the presence of ethephon as well as with PAT inhibitor 1-n-Naphthylphthalamic acid (NPA) or PGR (cytokinin). Therefore, it was suggested that morphological mechanism for stimulation of shoot formation was similar for all types of b uds. However, ‘Showtime Diva’ did not produce multiple shoots beyond those derived from pre-existing axillary buds, irrespective of the presence or absence of ethephon as a stimulator for shoot formation. A range of experiments using laser ethylene detector ETD-300 carried out to quantify ethylene concentration in the headspace of culture vessels released from ethephon in the medium. Ethylene was supplied either as gaseous ethylene, at a concentration of 60 nL.L-1 or released from ethephon incorporated into the media, but only direct absorption of ethephon from the medium was effective to increase shoot formation. The unique characteristic of meristematic activity at nodes of ‘Little Pinkie’, was likely derived from cells differing in their sensitivity to the endogenous balance of phytohormones and, in particular, a low ratio of auxin: cytokinin. Therefore, low ratio of auxin: cytokinin was the hypothesized mechanism for increased shoot formation following the application of ethephon, NPA or cytokinin. Increased shoot formation in ‘Little Pinkie’ as a result of either ethephon or NPA applied through the culture medium, provided evidence to support the hypothesised inhibitory effect of ethephon on polar auxin transport (PAT). However, while basipetal transport of radiolabelled auxin (14C-IAA) was inhibited by NPA, ethephon unexpectedly did not affect it. Rather than the direct inhibition on PAT, ethylene is suggested to have reduced auxin synthesis and/or changed its metabolism. In doing so, the reduction in endogenous concentration of auxin by ethephon or NPA, as well as any increase in endogenous content of cytokinin, could be responsible for the hypothesised reduction in the ratio of auxin: cytokinin and increased shoot formation.
Author may be contacted at: keshavarzi.hort@gmail.com
Keywords: Gentians; Effect of ethphon on; Ethephon; Growth; Plant regulators; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Horticulture